Virus diseases of groundnut - Sreenivasulu, P.; Reddy, C.V.; Ramesh, B.; Kumar, P. Lava (2008)
Groundnut or peanut is an important annual oilseed and food legume crop grown in diverse environments throughout the tropical world. About 31 viruses representing 14 genera were reported to naturally infect groundnut in different parts of the world. Among these, Tomato spotted wilt virus (TSWV), Groundnut bud necrosis virus (GBNV), Tobacco streak virus (TSV), Groundnut rosette assistor virus (GRAV), Groundnut rosette virus (GRV), satellite RNA associated with GRV and/or GRAV, Peanut clump virus (PCV), Peanut stripe virus (PStV), a strain of Bean common mosaic virus (BCMV), Peanut mottle virus (PeMoV) and Cucumber mosaic virus (CMV) have either global / regional economic importance. Cowpea aphid-borne mosaic virus (CABMV), CMV, IPCV, PCV, PeMoV, PStV, PSV and Cowpea mild mottle virus (CPMMV-severe strain) are transmitted through groundnut seed and thus are important quarantine pests. A review on the distribution, incidence, symptoms, impact on crop growth and yield, virus properties, phylogenetic relationships, virus detection, epidemiology and management of TSWV, GBNV, TSV, rosette complex, peanut clump, PStV, PeMoV and CMV, is presented in this chapter.